Environmental Security in South-Asia - Pandey, Chandra (Journal of International Affairs, 2016)
The proposition that climate change will engender anxieties for international security has become profound in public discourse over two decades. This paper discusses the concerns of environmental security in South Asia. It examines different meanings of environmental security to explain how it is associated with national security of the states in the region. Three major factors of environmental security problems are considered. Firstly, how environmental change can affect human security. Secondly, how environmental change can turn into violent conflict and thirdly, how the combined impact of these two variables affect the developmental concerns and national security of the individual state in South Asia.